A Global Supply Chain Security Management Strategy under U.S. Federal Law - Lizak, Robert (PRAWO i WIĘŹ, 2025)
Since the trade war between the United States (U.S.) and the People's Republic of China (PRC) began in 2018, the role of global supply chains has increased significantly, as reflected in U.S. federal law. This paper aims to test the hypothesis that supply chain management security is one of the most crucial components of the US global supply chain management strategy. This security can be significantly bolstered by overcoming three dominant challenges: resilience, variability and complexity. These challenges have found their way not only into public policies, but also into federal law, forming the basis of a strategic approach. Systematic planning, implementation and coordination activities are developed, with artificial intelligence being used for predictive, adaptive and data integration purposes, thus enabling a redefinition of US global supply chains.